Independent impact of gout on the risk of diabetes mellitus among women and men: a population-based, BMI-matched cohort study. Issue 1 (2nd October 2014) - Rho, Young Hee; Lu, Na; Peloquin, Christine E; Man, Ada; Zhu, Yanyan; Zhang, Yuqing; Choi, Hyon K
Abstract : Objective: Evidence on the potential independent impact of gout on the risk of diabetes is limited to a single study of men with a high cardiovascular risk profile. Our objective was to examine this relation in the general population, particularly among women. Methods: We conducted a sex-stratified matched cohort study using data from The Health Improvement Network (THIN), an electronic medical records database representative of the UK general population. Up to five non-gout individuals were matched to each case of incident gout by year of birth, year of enrolment and body mass index (BMI). Multivariate HRs for incident diabetes were calculated after additionally adjusting for smoking, alcohol consumption, physician visits, comorbidities and medication use. Results: Among 35 339 gout patients (72.4% men, mean age of 62.7 years), the incidence rates of diabetes in women and men were 10.1 and 9.5 cases per 1000 person-years, respectively, whereas the corresponding rates were 5.6 and 7.2 cases per 1000 person-years among 137 056 non-gout subjects. The BMI-matched univariate and multivariate HRs of diabetes were higher among women compared with those among men (1.71; 95% CI 1.51 to 1.93 vs 1.22; 95% CI 1.13 to 1.31) and (1.48; 95% CI 1.29 to 1.68 vs 1.15; 95% CI 1.06 to 1.24), respectively (p values for interaction <0.001). This sex difference persisted across age-specific subgroups. Conclusions: This general population-based study suggests that gout may be independently associated with an increased risk of diabetes and that the magnitude of association is significantly larger in women than in men.